Interactions between Vaccinia Virus IEV Membrane Proteins and Their Roles in IEV Assembly and Actin Tail Formation - Röttger, Sabine (American Society for Microbiology, 1999)
The intracellular enveloped form of vaccinia virus (IEV) induces the formation of actin tails that are strikingly similar to those seen in Listeria and Shigella infections. In contrast to the case for Listeria and Shigella, the vaccinia virus protein(s) responsible for directly initiating actin tail formation remains obscure. However, previous studies with recombinant vaccinia virus strains have suggested that the IEV-specific proteins A33R, A34R, A36R, B5R, and F13L play an undefined role in actin tail formation. In this study we have sought to understand how these proteins, all of which are predicted to have small cytoplasmic domains, are involved in IEV assembly and actin tail formation. Our data reveal that while deletion of A34R, B5R, or F13L resulted in a severe reduction in IEV particle assembly, IEVs formed by the ΔB5R and ΔF13L deletion strains, but not ΔA34R, were still able to induce actin tails. The ΔA36R deletion strain produced normal amounts of IEV particles, although these were unable to induce actin tails. Using several different approaches, we demonstrated that A36R is a type Ib membrane protein with a large, 195-amino-acid cytoplasmic domain exposed on the surface of IEV particles. Finally, coimmunoprecipitation experiments demonstrated that A36R interacts with A33R and A34R but not with B5R and that B5R forms a complex with A34R but not with A33R or A36R. Using extracts from ΔA34R- and ΔA36R-infected cells, we found that the interaction of A36R with A33R and that of A34R with B5R are independent of A34R and A36R, respectively. We conclude from our observations that multiple interactions between IEV membrane proteins exist which have important implications for IEV assembly and actin tail formation. Furthermore, these data suggest that while A34R is involved in IEV assembly and organization, A36R is critical for actin tail formation.